2018
DOI: 10.4336/2018.pfb.38e201701501
|View full text |Cite
|
Sign up to set email alerts
|

Weight is a key factor in the physiological quality of Parapiptadenia rigida seeds

Abstract: The objective of this work was to evaluate hygroscopicity modification of Eucalyptus dunnii, E. saligna and Corymbia maculata wood due to termites attack. Using samples measuring 20 x 20 x 150 mm³ (tangential x radial x longitudinal) the equilibrium moisture content (MCE), linear contractions of the tangential and radial planes (βT e βR), contraction anisotropy (CAβ), water absorption (AA) and water absorption rate (TAA) of healthy and deteriorated wood by Nasutitermes termites were evaluated. It was verified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…The correlation lines also differed between the populations, while population I had an almost steady value, with a low correlation index, population II had a positive correlation and substantially higher coefficient of determination ( Figure 4). Previous analysis indicated that greater seed weight promoted faster germination rates to Parapiptadenia rigida, another member of the Fabaceae family [7]. When considering the populations isolated, to population I, the relationship between seed weight and time required for germination is positive.…”
Section: Seed Weight and Germinationmentioning
confidence: 94%
See 4 more Smart Citations
“…The correlation lines also differed between the populations, while population I had an almost steady value, with a low correlation index, population II had a positive correlation and substantially higher coefficient of determination ( Figure 4). Previous analysis indicated that greater seed weight promoted faster germination rates to Parapiptadenia rigida, another member of the Fabaceae family [7]. When considering the populations isolated, to population I, the relationship between seed weight and time required for germination is positive.…”
Section: Seed Weight and Germinationmentioning
confidence: 94%
“…Thus, the great genetic diversity of these species [38], [39] is generally pointed out as the mean cause. However, seed growth is also influenced by environmental cues [7], [9], [40] such as edaphoclimatic differences [9] and ecologic interactions [4].…”
Section: Page|mentioning
confidence: 99%
See 3 more Smart Citations